Antibody Titers Reactive With Rickettsia rickettsii in Blood Donors and Implications for Surveillance of Spotted Fever Rickettsiosis in the United States. (2nd July 2019) - Straily, Anne; Stuck, Shawna; Singleton, Joseph; Brennan, Skyler; Marcum, Stephanie; Condit, Marah; Lee, Christopher; Kato, Cecilia; Tonnetti, Laura; Stramer, Susan L; Paddock, Christopher D
Abstract: Background: Since 2000, the reported prevalence of tick-borne spotted fever rickettsiosis has increased considerably. We compared the level of antibody reactivity among healthy blood donors from 2 widely separated regions of the United States and evaluated the impact of antibody prevalence on public health surveillance in one of these regions. Methods: Donor serum samples were evaluated by indirect immunofluorescence antibody assay to identify immunoglobulin G (IgG) antibodies reactive with Rickettsia rickettsii. The Georgia Department of Public Health (GDPH) analyzed characteristics of cases from 2016 surveillance data to evaluate the utility of laboratory surveillance for case assessment. Results: Of the Georgia donors (n = 1493), 11.1% demonstrated antibody titers reactive with R. rickettsii at titers ≥64, whereas 6.3% of donors from Oregon and Washington (n = 1511) were seropositive. Most seropositive donors had a titer of 64; only 3.1% (n = 93) of all donors had titers ≥128. During 2016, GDPH interviewed 243 seropositive case patients; only 28% (n = 69) met inclusion criteria in the national case definition for spotted fever rickettsiosis. Conclusions: These findings suggest that a single IgG antibody titer is an unreliable measure of diagnosis and could inaccurately affect surveillance estimates that define magnitude and clinical characteristics of Rocky Mountain spotted fever and other spotted fever rickettsioses. Abstract : A single immunoglobulin G antibody titer is an unreliable measure of diagnosis for spotted fever group rickettsiosis (SFGR) and could inaccurately affect surveillance estimates that define magnitude and clinical characteristics of SFGR in the United States.